KETERSEDIAAN RUANG TERBUKA HIJAU PUBLIK (STUDI KASUS DI KOTA PONTIANAK, 2016) - Kusnadi, Ari; Anwari, M Sofwan; Sisillia, Lolyta (Universitas Tanjungpura, 2017)
The urban growth at this time indicates unbalance movement activities, where many of it must be able to maintain and ensure its sustainability of resources and preservation of environmental quality. To minimize the negative impact of the environmental hazards against physical development in urban area is through green open space planning. The purpose of this study was to identify and analyze the needs and availability of green open space in Pontianak city in 2016 based on the area. The results showed that the availability of green open space in Pontianak city was 1,190 ha and the need of green open space was 2.156 ha (20% of area)Keywords: Availability, green open space, needs